PROBLEMATIKA PEMBELAJARAN BAHASA INDONESIA DI JENJANG SEKOLAH DASAR - saptono hadi (Fakultas Tarbiyah, Universitas Ibrahimy, 2019)
Indonesian language is an important language for Indonesian peoples as a differentiator from other nations. Therefore, it is the compulsory lesson in schools for all types and levels of schools in this country. This has become the formal language for citizens but there are students who have difficulty in learning this language. There are many problems in teaching Indonesian language experienced by teachers in schools. This phenomenon requires teachers to think hard to find solutions and try to overcome those problems. This article will examine those problems and offer solutions that can be done to resolve them specifically for elementary school students.